(3aQGFO GdeYGfi aj TQM MQR GdCeGfis - (3CHh YHO Gddg eMeO Hf hGhO GdUfgGLi GdeYQha HGHf CLQhes; (3bGSe Hf ajQg GdTGWHj, CHh eMeO,J (B590 (3g` s
(3ChdgG (B:s
(3jbhd eMeO GdUfgGLi YaG Gddg Yfg GdMeO ddg GdeHJOF HGdEMSGf CeG HYO aEf GdYde CQaY GdeWGdH s
(3BNQgG (B:s
(3hjDNP ef bhd GdfGXe CUM JbHdG Cf gfGdc hLg BNQ Ohfg ai GdUMI hgh fbd GdMQcI aGYde Pdc HGddg GdJhajb s
(3GdfSNI HgG MhGTs
(3JHUQGJ GdCUd (B:s
(3GdfSNI HNW GdeDda GdfSNI eYGQVI Ydi fSNI GdeDpqdas
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(146(3b(B) s
Keywords: (3GdbQGAGJ hGdJLhjOs